Funciones desempeñadas como Administrador de Agencia, en la Cooperativa de Ahorro y Crédito San Martín de Porres Ltda, periodo 2014 a 2017 - Requejo Quispe, Luis Alberto (2019)
The present report of professional proficiency was developed by the San Martin de Porres association of savings and credits San José de Sisa Agency, in the province of El Dorado, San Martin región. Covers the 2014-2017 years and have as general porpouse, identify and analyze the main ecomic indicators in the San Martin de Porres association of savings and credits agency at the year 2017. After presenting the main functions of the agency's administrator, the problem was mainly identified in the management of the main economic indicators, like: slow growth of the remnants, low sell placement, high peding debts and few captures of savings. In addition, problems were established in personnel management and associative management. To solve this problems, the next actions was taken: Policies were applied to prioritize the satisfaction of the partner around their credit expectations, the process to optimize the time management were improved to increase the value and minimize the effort, the communications were improved to reduce the miss information, achieving greater commitment between the parties and developing good human relationships to take advantage of the competences and the human talent of the colaborators. Finally, the conclusions respond to the objectives of the personal sufficiency report, emphasizing the results achieved, these are: the remnants reach their historic record of the agency with 426 556 soles. The sell placements were increase in 35.57%, the partners in 12.25%, savings in 72.28%, assets 34.39%. The pending debts rate historically low to 3.45%.